Analysing UTAUT in flipped learning implementation - Abd Rahman, Siti Fatimah; Md Yunus, Melor; Hashim, Harwati (2019)
The flipped learning approach focuses on meaningful learning and it is based on responsibility shared by educators and learners. Flipped learning also authorises learners to take an engaging role in learning whilst educators facilitate the learning process. While the implementation of flipped learning has proven to enhance ESL teaching and learning in the previous studies, flipped learning in terms of Malaysian ESL lecturers in public universities has yet to be explored. This study aims to explore the utilization of Unified Theory of Technology Acceptance and Use of Technology (UTAUT) towards Malaysian ESL lecturers’ attitude in implementing flipped learning. This study employs a quantitative research where a set of online questionnaire is used in collecting the data. Four public universities are chosen and 206 ESL lecturers participated in this study. The data was analysed using structural equation modelling (SEM). The result of this study indicates that performance expectancy and effort expectancy are the strong predictors in predicting Malaysian ESL lecturers’ attitude towards the implementation of flipped learning. Furthermore, this study enriches the literature in 21st century education as well as the integration of technology in teaching and learning. In addition, this study could help educators and stakeholders in adapting or enhancing the flipped learning approach by distinguishing the distinct predictors in technology acceptance.